Factors Affecting Musculoskeletal Disorders in Silk Preparation Process Workers in the Silk Weaving Profession in Buriram Province - Noyming, Sombut; Nachaikong, Pongsak; Loatong, Poranee; Parichatnon, Kamonthip; Parichatnon, Surakiat; Rithinyo, Manote (Asian Health, Science and Technology Reports, 2023)
Musculoskeletal disorders in workers of the silk weaving professions have become a significant problem affecting production effectiveness. The objectives of this study were to explore the prevalence rate and factors affecting the musculoskeletal disorders of 400 female silk preparation process workers in the silk weaving profession in Buriram province. The data was collected by using questionnaires derived from the standardized Nordic questionnaire and the musculoskeletal disorders evaluation form developed by the Department of Disease Control, Ministry of Health, Thailand. The data were analyzed by descriptive statistics and binary logistic regression. The results revealed that 92% of the silk preparation professionals had problems with muscle pains mainly in their lower back and 91.75% had knees pain. Buttock and hip pain were experienced by 90.50% of the workers, and 90.25% had left and right shoulder pain. Factors affecting the musculoskeletal disorders were: 1) age, 2) working time, 3) break time, 4) reaching above the shoulder to pick up or hold the material, 5) continuous bending down of their heads to work, 6) hands or arms working in repetitive movements (for at least 30 minutes). Thus, this study identifies factors affecting MSDs among workers and gains a greater understanding of working posture according to ergonomics which may help in maintaining the health and safety of workers, and hence leading to increased work productivity and efficiency.